ENGAGING THE STUDENTS WITH STYLES IN EFL PERSPECTIVES - Atik Sri Rahayu (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
The active participation of students in the classroom is considered as the essential component in the learning. It is closely related to the students’ engagement, which involves the students’ interest, positive attitude and enjoyment towards learning. One crucial factor which influences the students’ engagement in the classrooms is the teachers’ teaching styles. The teachers’ behaviors, beliefs and personality in teaching really influence their styles in teaching. Therefore, teaching styles become crucial since it can build and shape the students’ learning experience in the classrooms.